Intra-Arterial Stem Cell Transplantation in Experimental Stroke in Rats: Real-Time MR Visualization of Transplanted Cells Starting With Their First Pass Through the Brain With Regard to the Therapeutic Action - Namestnikova, Daria D.; Gubskiy, Ilya L.; Revkova, Veronica A.; Sukhinich, Kirill K.; Melnikov, Pavel A.; Gabashvili, Anna N.; Cherkashova, Elvira A.; Vishnevskiy, Daniil A.; Kurilo, Victoria V.; Burunova, Veronica V.; Semkina, Alevtina S.; Abakumov, Maxim A.; et al. (Frontiers in Neuroscience, 2021)
Cell therapy is an emerging approach to stroke treatment with a potential to limit brain damage and enhance its restoration after the acute phase of the disease. In this study we tested directly reprogrammed neural precursor cells (drNPC) derived from adult human bone marrow cells in the rat middle cerebral artery occlusion (MCAO) model of acute ischemic stroke using human placenta mesenchymal stem cells (pMSC) as a positive control with previously confirmed efficacy. Cells were infused into the ipsilateral (right) internal carotid artery of male Wistar rats 24 hours after MCAO. The main goal of this work was to evaluate real-time distribution and subsequent homing of transplanted cells in the brain. This was achieved by performing intra-arterial infusion directly inside the MRI scanner and allowed transplanted cells tracing starting from their first pass through the brain vessels. Immediately after transplantation, cells were observed in the periphery of the infarct zone and in the brain stem, 15 minutes later small numbers of cells could be discovered deep in the infarct core and in the contralateral hemisphere, where drNPC were seen earlier and in greater numbers than pMSC. Transplanted cells in both groups could no longer be detected in the rat brain 48-72 hours after infusion. Histological and histochemical analysis demonstrated that both the drNPC and pMSC were localized inside blood vessels in close contact with the vascular wall. No passage of labeled cells through the blood brain barrier was observed. Additionally, the therapeutic effects of drNPC and pMSC were compared. Both drNPC and pMSC induced substantial attenuation of neurological deficits evaluated at the 7th and 14th day after transplantation using the modified neurological severity score (mNSS). Some of the effects of drNPC and pMSC, such as the influence on the infarct volume and the survival rate of animals, differed. The results suggest a paracrine mechanism of the positive therapeutic effects of IA drNPC and pMSC infusion, potentially enhanced by the cell-cell interactions. Our data also indicate that the long-term homing of transplanted cells in the brain is not necessary for the brain’s functional recovery.